KECENDERUNGAN PERILAKU BULLYING DITINJAU DARI HARGA DIRI DAN MASKULINITAS PADA REMAJA - , Sugiariyanti, S.Psi., Dr. M. G. Adiyanti, M. S. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Violence and aggression in schools are a problem in many countries around the world. One form of aggression that takes place at school is bullying. Bullying is an interaction in which a dominant individual (the bully) repeatedly exhibits aggressive behaviour intended to cause distress to a less dominant individual (the victim). The present study examined the relationships between self esteem, masculinity and bullying among adolescents. The participants were 11th grade students of Vocational High Schools, 140 boys, 16-18 years old (mean age = 16,5 years). They completed three scales measuring self esteem, masculinity and the tendency to bully others. The data were analyzed by multiple regression analysis to look at the relationship between variables. The results showed that 1) self-esteem and masculinity was jointly significant in predicting the tendency of bullying behavior among adolescents. Effective contribution of the self-esteem and masculinity simultaneously in predicting the tendency of bullying behavior at 28.4%